RNA-Seq Analysis Provides the First Insights into the Phylogenetic Relationship and Interspecific Variation between Agropyron cristatum and Wheat - Zhou, Shenghui; Yan, Baiqiang; Li, Fei; Zhang, Jinpeng; Zhang, Jing; Ma, Huihui; Liu, Weihua; Lu, Yuqing; Yang, Xinming; Li, Xiuquan; Liu, Xu; Li, Lihui (Frontiers in Plant Science, 2017)
Agropyron cristatum, which is a wild grass of the tribe Triticeae, grows widely in harsh environments and provides many desirable genetic resources for wheat improvement. However, unclear interspecific phylogeny and genome-wide variation has limited the utilization of A. cristatum in the production of superior wheat varieties. In this study, by sequencing the transcriptome of the representative tetraploid A. cristatum Z559 and the common wheat variety Fukuhokomugi (Fukuho), which are often used as parents in a wide cross, their phylogenetic relationship and interspecific variation were dissected. First, 214,854 transcript sequences were assembled, and 3,457 orthologous genes related to traits of interest were identified in A. cristatum. Second, a total of 72 putative orthologous gene clusters were used to construct phylogenetic relationships among A. cristatum, Triticeae and other genomes. A clear division between A. cristatum and the other Triticeae species was revealed. Third, the sequence similarity of most genes related to traits of interest is greater than 95% between A. cristatum and wheat. Therefore, using the 5% mismatch parameter for A. cristatum, we mapped the transcriptome sequencing data to wheat reference sequences to discover the variations between A. cristatum and wheat and 862,340 high-quality variants were identified. Additionally, compared with the wheat A and B genomes, the P and D genomes displayed an obviously larger variant density and a longer evolutionary distance, suggesting that A. cristatum is more distantly related to the wheat D genome. Finally, by using Kompetitive Allele Specific PCR array (KASPar) technology, 37 of 53 (69.8%) SNPs were shown to be genuine in Z559, Fukuho, and additional lines with seven different P chromosomes, and function of the genes in which these SNPs are located were also determined. This study provides not only the first insights into the phylogenetic relationships between the P genome and Triticeae but also genetic resources for gene discovery and specific marker development in A. cristatum, and this information will be vital for future wheat-breeding efforts. The sequence data have been deposited in the Sequence Read Archive (SRA) database at the NCBI under accession number SRP090613.